Linguistics Theories, Nigerian Languages, and the Quest for Development (2023)
This work assesses the progression of African linguistics and the application of theories to the study of African languages in light of the developmental needs of the languages. It is observed that the vast majority of African languages are yet to be adequately described for human learning and generational transmission. However, as linguists continue to adopt theories driven by language computations, descriptions needed for human learning seem to become expendable, a reality amounting to doing linguistics for the machine at the expense of humans. With attention now shifting to computation-motivated approaches, further development that can make these languages suitable for science education, security, law, medical practices and other contemporary realities in Nigerian society tends to be less rigorously pursued. Apart from Hausa, Igbo and Yoruba, there is minimal progress being made in terms of the development of Nigerian languages. Standard dictionaries and other materials designed to aid the deployment of the languages to meet contemporary human needs within the speech communities are rarely produced in the languages. This is despite the quantum of linguistic work being done. When this is viewed in light of the endangered status of the languages, it projects a critical situation. It is concluded that there is a need for synergy between linguistics for human use and the machine. This can only be championed by African linguists with the developmental needs of African languages as objective.